2013
DOI: 10.1289/ehp.1205894
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in World Trade Center Rescue and Recovery Workers, 2001–2008

Abstract: Background: World Trade Center (WTC) rescue and recovery workers were exposed to a complex mix of pollutants and carcinogens.Objective: The purpose of this investigation was to evaluate cancer incidence in responders during the first 7 years after 11 September 2001.Methods: Cancers among 20,984 consented participants in the WTC Health Program were identified through linkage to state tumor registries in New York, New Jersey, Connecticut, and Pennsylvania. Standardized incidence ratios (SIRs) were calculated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
149
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(159 citation statements)
references
References 25 publications
9
149
1
Order By: Relevance
“…They found excess thyroid cancer incidence in a group of occupations including protective services, construction, building and ground cleaning and maintenance, electrical, telecommunications and other installation and repair groups (CM&IRG); and all other occupations related to the rescue and recovery work of WTC compared to the incidence of general population in the United States. However, the increased risk was not observed when limited those working in protective services group and CM&IRG (40). Pukkala et al (23) reported a significantly increased risk of thyroid cancer in female building care takers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They found excess thyroid cancer incidence in a group of occupations including protective services, construction, building and ground cleaning and maintenance, electrical, telecommunications and other installation and repair groups (CM&IRG); and all other occupations related to the rescue and recovery work of WTC compared to the incidence of general population in the United States. However, the increased risk was not observed when limited those working in protective services group and CM&IRG (40). Pukkala et al (23) reported a significantly increased risk of thyroid cancer in female building care takers.…”
Section: Discussionmentioning
confidence: 95%
“…Few studies have highlighted the association between building cleaning, ground cleaning, and maintenance occupations and thyroid cancer. Solan et al (40) examined cancer incidence in World Trade Center (WTC) rescue and recovery workers during the first seven years after September 11, 2001. They found excess thyroid cancer incidence in a group of occupations including protective services, construction, building and ground cleaning and maintenance, electrical, telecommunications and other installation and repair groups (CM&IRG); and all other occupations related to the rescue and recovery work of WTC compared to the incidence of general population in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The overlaps in participants among the three programs ranged from less than 1% between the WTC-HP and FDNY to approximately 20% for responders between the Registry and WTC-HP [27]. The total number of FDNY participants ranged from 1159 to 8869 for each of the nine survey cycles between 2001 and 2010 [6].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have considered the relationship between iodine intake and TC risk, but their results are rather inconclusive203031. Endocrine disrupting compounds such as polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs) and pesticides, which can disturb thyroid function, have been linked to carcinogenesis through a variety of mechanisms323334. TC is gender-biased, i.e., it is more common among females than among males with a female to male ratio of about 3 to 1 in the general population35.…”
mentioning
confidence: 99%
“…While stochastic associations do not usually imply necessary and sufficient causation criteria, they offer useful insight into such a complicated situation of considerable public health significance3244. Studies of disease associations in human populations involve a variety of techniques, including visual comparisons of the patterns exhibited by the disease factors, statistical analysis of population disease occurrences across a geographic area, multi-perspective analysis, and geographical information systems techniques304546474849.…”
mentioning
confidence: 99%